Synthesis of Nickel Nitride‐Based 1D/0D Heterostructure via a Morphology‐Inherited Nitridation Strategy for Efficient Electrocatalytic Hydrogen Evolution. Issue 25 (20th May 2022) - Wang, Bin; Guo, Lingju; Zhang, Jiangwei; Qiao, Yuyan; He, Meng; Jiang, Qike; Zhao, Yang; Shi, Xinghua; Zhang, Fuxiang
Abstract: The fabrication of heterostructures has inspired extensive interest in promoting the performance of solar cells or solar fuel production, but it is still challenging for nitrides to prepare structurally ordered heterostructures. Herein, one nickel nitride‐based heterostructure composed of 1D Ni0.2 Mo0.8 N nanorods and 0D Ni3 N nanoparticles (denoted as NiMoN/NiN) is reported to exhibit significantly promoted hydrogen evolution reaction performance in both alkaline and neutral media. In particular, the optimal overpotential of the NiMoN/NiN sample at 10 mA cm −2 in 1 m KOH is 49 mV. The successful fabrication of 1D/0D heterostructures is mainly ascribed to morphology‐inherited nitridation of 1D oxide precursor (denoted as NiMoO‐NRs) in situ grown on Ni foam surface, and attributed to strong Lewis acid–base interaction that renders the Ni 2+ ions emitted from the oxide precursor to well coordinate with NH3 for the formation of Ni3 N nanoparticles during the nitridation process. It is theoretically and experimentally demonstrated that the special 1D/0D heterostructure provides tandem active phases Ni0.2 Mo0.8 N and Ni3 N for synergistic promotion in lowering the activation energy of H2 O dissociation and optimizing the adsorption energy of H, respectively. This work may open a new avenue for developing highly active tandem electrocatalysts for promising renewable energy conversion. Abstract : The successful fabrication of one nickel nitride‐based heterostructure composed of 1D Ni0.2 Mo0.8 N nanorods and 0D Ni3 N nanoparticles via morphology‐inherited nitridation coupled with NH3 ‐induced nickel emission strategies is reported. The 1D/0D heterostructure exhibits highly efficient hydrogen evolution reaction in both alkaline and neutral media. The distinct functional advantages of heterostructures render them to be good partners of the tandem electrocatalyst.